Cost-effectiveness of biological treatment of ulcerative colitis – a systematic review - Stawowczyk, Ewa; Kawalec, Paweł (Gastroenterology Review/Przegląd Gastroenterologiczny, 2017)
The aim of this systematic review was to collect and summarise all current data on the cost-effectiveness of biological treatment in ulcerative colitis. A literature search was conducted using the Medline, Embase, Centre for Reviews and Dissemination databases and included all cost-effectiveness analyses comparing biological treatment with any comparator. We identified 277 records of which 10 were included in this review. Eighty percent of identified analyses used quality-adjusted life years (QALY) as a measure of outcome. The most commonly assessed biological agent was infliximab. Half of the eight economic analyses, with QALY as an outcome, showed the cost-effectiveness of biological treatment against the comparator. Incremental cost-effectiveness ratios (ICER) ranged from 15,748 euro to 450,791 euro. The highest ICER values were observed when biologicals were compared with standard care alone. This systematic review revealed that in some cases the biological treatment, despite its clinical effectiveness, is too expensive and exceeds the national threshold value.